Urban heritage streets revitalisation : identification of attributes and development of ranking and strategy / Zalina Samadi - Samadi, Zalina (Institute of Graduate Studies, UiTM, 2015)
This study focuses on the revitalisation performance of the outdoor ambience in between heritage streets. The heritage streets in this study is limited to an abundance of shop houses within the core zone of the historic city of the Straits of Malacca; George Town in Pulau Pinang and Melaka. The existing physical and spiritual attributes of the ‘outdoor space in between the heritage street is currently in various conditions that requires urgent monitoring system of revitalisation. The spaces have a high potential to be enhanced as ‘an urban outdoor living room’ with magnetic attraction as “a place” for promoting on-street cultural heritage products and environment. The vibrancy of pedestrian movement of the observed study area has the regenerative potentials to create a positive aura with unique, antique and authentic ambience…